Peningkatan penjualan produk UMKM melalui edukasi digital marketing berbasis media sosial di Desa Karangbong - Karina Zakiatul Skiah; Nandhita Putri Maulaniah; Anisa Nurul Wilda (P3HKI - Universitas Muhammadiyah Parepare, 2024)
This community service activity was motivated by the limited utilization of digital media in product marketing by micro, small, and medium enterprises (MSMEs) in Karangbong Village, Pajarakan Sub-district, Probolinggo Regency. Most MSME actors still rely on traditional marketing strategies, such as passively waiting for customers to visit their business locations. The objective of this program was to provide education and assistance to MSME actors to optimize their marketing strategies through digital platforms, particularly Instagram. The implementation methods included initial observation, interviews with MSME actors and village officials, delivery of training materials, and hands-on assistance in creating promotional content and managing social media accounts. A total of 34 MSME actors were involved in this program, with 10 actively participating in the mentoring process. The results of the activity indicated an improvement in participants' understanding of digital marketing strategies, social media account management, and the ability to design and schedule engaging promotional content. This initiative is expected to foster the sustainability of digital marketing practices among MSMEs and enhance their product competitiveness in broader markets.